Preparation method of molybdenum boron ion modified and cesium doped Li-Al hydrotalcite solid electrolyte

Through the preparation method of Li-Al hydrotalcite solid electrolyte with molybdenum boron ion modification and cesium doped Li-Al hydrotalcite solid electrolyte, the defects in ion conductivity and electrochemical performance of existing solid electrolyte materials are solved, and efficient ion transport and improved thermal stability are achieved.

CN119674198APending Publication Date: 2025-03-21ZHEJIANG LINGYI NEW ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411845736.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing solid-state electrolyte materials have defects in ionic conductivity, interface contact capability, interface stability and sensitivity to air, making it difficult to meet the high-performance needs of solid-state batteries.

Method used

The preparation method of solid electrolyte with molybdenum boron ion modified and cesium-doped Li-Al hydrotalcite is prepared by hydrothermal method, and then the boron ions and molybdenum ions are injected into the electrolyte sheet using plasma technology to form a modified electrolyte.

Benefits of technology

It improves the ionic conductivity and lithium ion mobility of solid electrolytes, improves the thermal stability and electrochemical properties of materials, and enhances its application performance in batteries or electrolytes.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a preparation method of a molybdenum boron ion modified and cesium doped Li-Al hydrotalcite solid electrolyte, in the process of Cs < + > doped Li-Al hydrotalcite, a part of lithium ions are replaced by cesium ions, resulting in the change of lattice parameters, the introduction of boron, and the expansion of the space between hydrotalcite layers, so that the stability of the electrolyte is improved. The interlayer spacing is increased, a non-uniform pore structure is formed to promote ion movement, amino groups introduced through ammonia gas treatment and allyl boronic acid pinacol ester are subjected to an amino-acrylic acid addition reaction, functional groups of hydrotalcite are increased, plasma treatment is carried out by using molybdenum hexacarbonyl steam, and the surface area of the hydrotalcite is increased. Boron ions and molybdenum ions are injected into the electrolyte sheet, the mechanical strength and chemical stability of the material are enhanced, meanwhile, a new electrochemical active center is introduced for hydrotalcite, and the electrochemical performance of the material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium battery solid electrolytes, and specifically relates to a method for preparing a molybdenum-boron ion-modified and cesium-doped Li-Al hydrotalcite solid electrolyte. Background Art

[0002] Solid-state batteries have great development prospects due to their high energy density and high safety, and the development of solid-state electrolytes with high ionic conductivity is a key issue in the development of solid-state batteries.

[0003] Patent CN115224355A discloses a copper-doped solid electrolyte, its preparation method and application, and all-solid-state battery. The method comprises: (1) pressing an oxide electrolyte into a shape to obtain a solid electrolyte sheet; (2) stacking the solid electrolyte sheet and copper foil in an oxygen-containing atmosphere to form a solid electrolyte precursor, and calcining the solid electrolyte precursor; the calcination conditions at least include: a heating rate of 1-5°C / min, a temperature of 600-1300°C, and a time of 1-24h.

[0004] Patent CN114744286A discloses an ion-doped solid electrolyte membrane and its preparation method and application, wherein the preparation method comprises the steps of: providing a sulfide electrolyte membrane; injecting metal cations and oxygen group anions into the sulfide electrolyte membrane using plasma technology to obtain an ion-doped solid electrolyte membrane.

[0005] The electrolyte materials studied previously all have different disadvantages, such as low ionic conductivity of polymer systems, poor interface contact ability and interface stability of oxide systems, and sulfides are extremely sensitive to air and prone to produce toxic gases. There are more types of new materials with application potential in the field of solid electrolytes, waiting for people to explore. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing a cesium-doped Li-Al hydrotalcite solid electrolyte modified by molybdenum-boron ions. The hydrotalcite intercalation material (hydrotalcite) is a non-conductive layered compound, and its structure is conducive to its modification. Part of the lithium ions are replaced by cesium ions, thereby improving the ionic conductivity. The technical solution of the present invention is: a Cs + The preparation method of the Li-Al doped hydrotalcite solid electrolyte comprises the following steps:

[0007] 1. A method for preparing a molybdenum-boron ion modified, cesium-doped Li-Al hydrotalcite solid electrolyte, characterized by comprising the following steps:

[0008] A.Cs +Preparation of doped Li-Al (lithium aluminum hydrotalcite material): Li-Al hydrotalcite was prepared by hydrothermal method. Appropriate amount of Al(OH)3 (analytical grade), LiCl (analytical grade), CsCl (analytical grade) and deionized water were used as raw materials for hydrothermal reaction. The reactor was taken out and cooled to room temperature. The sample was washed after centrifugation. The solid sample was collected and dried. Finally, the dried solid was ground and sieved out into fine powder to obtain Cs + Li-Al doped hydrotalcite powder.

[0009] B. Cs + The doped Li-Al hydrotalcite powder is placed in a tablet pressing mold, and the powder is pressed into an electrolyte sheet on a tablet press. The sheet is cut and finally stored in a glove box to prevent moisture. Boron ions and molybdenum ions are injected into the electrolyte sheet using plasma technology, and then assembled into a solid-state battery to test its ionic conductivity and lithium ion mobility.

[0010] As a preferred technical solution of the present invention, in step A, the mass ratio of Al(OH)3, LiCl, and CsCl is 1-2:4-6:0.05-0.3.

[0011] As a preferred technical solution of the present invention, in step A, the content of deionized water is 100-200 mL.

[0012] As a preferred technical solution of the present invention, in step A, the hydrothermal temperature is 80-100° C. and the drying time is 1-2 days.

[0013] As a preferred technical solution of the present invention, in step A, the sample is centrifuged and then washed three to five times with ice deionized water.

[0014] As a preferred technical solution of the present invention, in step B, the diameter of the electrolyte sheet is about 16-19 mm.

[0015] As a preferred technical solution of the present invention, in step B, the thickness is about 1-2 mm.

[0016] As a preferred technical solution of the present invention, in step B, the operating frequency of the plasma processing equipment is 13.56-40.68 MHz.

[0017] As a preferred technical solution of the present invention, in step B, the power of the plasma treatment is 500-2000 watts, and the treatment time is 1-5 minutes.

[0018] As a preferred technical solution of the present invention, in step B, during the plasma treatment process, the atmosphere in the treatment chamber is maintained as an inert gas with a gas flow rate of 50-100 ml / min.

[0019] Cs containing molybdenum and boron + Reaction mechanism of Li-Al doped hydrotalcite

[0020] Partial replacement of lithium ions: in Cs + During the process of doping Li-Al hydrotalcite, a part of the lithium ions are replaced by cesium ions, resulting in a change in the lattice parameters. This replacement changes the charge density and interaction force between the hydrotalcite layers, thereby affecting the electrochemical properties of the material.

[0021] Increase in interlayer spacing: Due to the introduction of boron, the space between the hydrotalcite layers is enlarged, which facilitates the migration and transport of ions in the electrolyte. After boron enters the Li / Al-hydrotalcite s-layer, various borate species are formed, which promote the movement of ions by increasing the interlayer spacing and forming a non-uniform pore structure.

[0022] Amino-acrylic acid addition reaction: The amine groups introduced by ammonia treatment undergo amino-acrylic acid addition reaction with propylene boric acid pinacol ester, which increases the functional groups of hydrotalcite and provides active sites for further chemical reactions.

[0023] Plasma treatment: Plasma treatment using molybdenum hexacarbonyl vapor allows boron and molybdenum ions to be injected into the electrolyte sheet, enhancing the mechanical strength and chemical stability of the material while also introducing new electrochemically active centers into the hydrotalcite.

[0024] Compared with the prior art, the present invention has the following advantages:

[0025] Improved ionic conductivity: Due to the increase in interlayer spacing and the introduction of new ions, the ionic conductivity of Cs+-doped Li-Al hydrotalcite is improved, which helps to improve its application performance in batteries or electrolytes.

[0026] Improved thermal stability and electrochemical performance: Combined with molybdenum and boron doping, the material's stability at high temperatures is enhanced, and its electrochemical performance is also improved due to the introduction of more active sites. These characteristics make the material more potential for application in energy storage and conversion devices. DETAILED DESCRIPTION

[0027] The present invention is described in detail below in conjunction with specific implementation modes.

[0028] Embodiment 1,

[0029] 1. A method for preparing a molybdenum-boron ion modified, cesium-doped Li-Al hydrotalcite solid electrolyte, characterized by comprising the following steps:

[0030] A.Cs +Preparation of doped Li-Al hydrotalcite: Li-Al hydrotalcite was prepared by hydrothermal method, using Al(OH)3 (analytical grade), LiCl (analytical grade) and deionized water as raw materials. 7.8g Al(OH)3, 16.96g LiCl, 0.421g CsCl and 100mL deionized water were placed in a reactor and heated at 80°C in a drying oven for 36h. The reactor was taken out and cooled to room temperature. The sample was centrifuged and washed three times with ice deionized water, and the solid sample was collected and dried. Finally, the solid was ground and sieved to obtain fine powder to obtain Cs + Li-Al doped hydrotalcite powder.

[0031] B. Cs + The Li-Al doped hydrotalcite powder was placed in a tableting mold and pressed into an electrolyte sheet on a tablet press at a pressure of about 500 MPa. The diameter of the electrolyte sheet was about 18 mm and the thickness was about 1.5 mm. + The doped Li-Al hydrotalcite electrolyte sheet was stored in a glove box to prevent moisture. Boron ions and molybdenum ions were injected into the electrolyte sheet using plasma technology. The plasma treatment equipment had an operating frequency of 13.56 MHz, a power of 500 watts, a treatment time of 1 minute, and a gas flow rate of 50 ml / min. The solid-state battery was assembled and its ion conductivity was tested to be 5.8×10 -5 S / cm, and the lithium ion mobility is 0.35.

[0032] Embodiment 2,

[0033] A method for preparing a molybdenum-boron ion-modified, cesium-doped Li-Al hydrotalcite solid electrolyte, characterized by comprising the following steps:

[0034] The difference from Example 1 is:

[0035] A.Cs + Preparation of doped Li-Al hydrotalcite: Li-Al hydrotalcite was prepared by hydrothermal method, using Al(OH)3 (analytical grade), LiCl (analytical grade) and deionized water as raw materials. 10g Al(OH)3, 21g LiCl, 1.2627g CsCl and 150mL deionized water were placed in a reactor and heated at 90°C in a drying oven for 24h. The reactor was taken out and cooled to room temperature. The sample was centrifuged and washed four times with ice deionized water, and the solid sample was collected and dried. Finally, the solid was ground and sieved out to obtain fine powder to obtain Cs + Li-Al doped hydrotalcite powder.

[0036] B. Cs +The Li-Al doped hydrotalcite powder was placed in a tableting mold and pressed into an electrolyte sheet on a tablet press at a pressure of about 600 MPa. The diameter of the electrolyte sheet was about 16 mm and the thickness was about 1 mm. + The doped Li-Al hydrotalcite electrolyte sheet was stored in a glove box to prevent moisture. Boron ions and molybdenum ions were injected into the electrolyte sheet using plasma technology. The plasma treatment equipment had an operating frequency of 20.68 MHz, a power of 1500 watts, a treatment time of 3 minutes, and a gas flow rate of 75 ml / min. The solid-state battery was assembled.

[0037] The ionic conductivity was tested to be 6.2×10 -5 S / cm, and the lithium ion mobility is 0.49.

[0038] Embodiment 3,

[0039] A method for preparing a molybdenum-boron ion-modified, cesium-doped Li-Al hydrotalcite solid electrolyte, characterized by comprising the following steps:

[0040] The difference from Example 1 is:

[0041] The mass of Al(OH)3 is 15.6 g and the mass of LiCl solution is 25.43 g. The hydrothermal reaction temperature is 100°C and the reaction time is 48 hours. The mass of CsCl is 2.5254 g (concentration is 0.3 mol / L).

[0042] Assembled into a solid-state battery, the ionic conductivity was tested to be 5.8×10 -5 S / cm, the lithium ion mobility is 0.35. A, Cs + Preparation of doped Li-Al hydrotalcite: Li-Al hydrotalcite was prepared by hydrothermal method, using Al(OH)3 (analytical grade), LiCl (analytical grade) and deionized water as raw materials. 15.6g Al(OH)3, 25.43g LiCl, 2.5254g CsCl and 200mL deionized water were placed in a reactor and heated at 100°C in a drying oven for 48h. The reactor was taken out and cooled to room temperature. The sample was centrifuged and washed five times with ice deionized water, and the solid sample was collected and dried. Finally, the solid was ground and sieved out to obtain fine powder to obtain Cs + Doped Li-Al hydrotalcite powder. B. + The doped Li-Al hydrotalcite powder was placed in a tableting mold and pressed into an electrolyte sheet on a tablet press at a pressure of about 700 MPa. The diameter of the electrolyte sheet was about 19 mm and the thickness was about 2 mm. +The doped Li-Al hydrotalcite electrolyte sheet was stored in a glove box to prevent moisture. Boron ions and molybdenum ions were injected into the electrolyte sheet using plasma technology. The plasma treatment equipment had an operating frequency of 40.68 MHz, a power of 2000 watts, a treatment time of 5 minutes, and a gas flow rate of 100 ml / min. The solid-state battery was assembled and its ion conductivity was tested to be 5.2×10 -4 S / cm and lithium ion mobility are 0.56.

[0043] Comparative Example 1

[0044] A method for preparing a molybdenum-boron ion-modified, cesium-doped Li-Al hydrotalcite solid electrolyte comprises the following steps:

[0045] A.Cs + Preparation of doped Li-Al hydrotalcite: Li-Al hydrotalcite was prepared by hydrothermal method, using Al(OH)3 (analytical grade), LiCl (analytical grade) and deionized water as raw materials. 7.8g Al(OH)3, 16.96g LiCl, 0.421g CsCl and 100mL deionized water were placed in a reactor and heated at 80°C in a drying oven for 36h. The reactor was taken out and cooled to room temperature. The sample was centrifuged and washed three times with ice deionized water, and the solid sample was collected and dried. Finally, the solid was ground and sieved to obtain fine powder to obtain Cs + Li-Al doped hydrotalcite powder.

[0046] B. Cs + The Li-Al doped hydrotalcite powder was placed in a tableting mold and pressed into an electrolyte sheet on a tablet press at a pressure of about 500 MPa. The diameter of the electrolyte sheet was about 18 mm and the thickness was about 1.5 mm. + The Li-Al-doped hydrotalcite electrolyte sheet was stored in a glove box to prevent moisture. It was assembled into a solid-state battery and its ionic conductivity was tested to be 4.5×10 -5 S / cm and lithium ion mobility are 0.22.

[0047] Comparative Example 2

[0048] A method for preparing a molybdenum-boron ion-modified, cesium-doped Li-Al hydrotalcite solid electrolyte comprises the following steps:

[0049] A. Preparation of Li-Al hydrotalcite: Li-Al hydrotalcite was prepared by hydrothermal method, using Al(OH)3 (analytical grade), LiCl (analytical grade) and deionized water as raw materials. 7.8g Al(OH)3, 16.96g LiCl, and 100mL deionized water were placed in a reactor and heated at 80°C in a drying oven for 36h. The reactor was taken out and cooled to room temperature, the sample was centrifuged and washed three times with ice deionized water, and the solid sample was collected and dried. Finally, the solid was ground and sieved out to obtain a fine powder to obtain Li-Al hydrotalcite powder.

[0050] B. Place the Li-Al hydrotalcite powder in a tableting mold and press the powder into an electrolyte sheet on a tablet press at a pressure of about 500 MPa. The diameter of the electrolyte sheet is about 18 mm and the thickness is about 1.5 mm. Finally, the pressed Li-Al hydrotalcite electrolyte sheet is placed in a glove box to prevent moisture. Boron ions and molybdenum ions are injected into the electrolyte sheet using plasma technology. The operating frequency of the plasma treatment equipment is 13.56 MHz, the power is 500 watts, the treatment time is 1 minute, the gas flow rate is 50 ml / min, and the solid-state battery is assembled. The ionic conductivity is tested to be 4.8×10 -5 S / cm, and the lithium ion mobility is 0.26.

Claims

1. A method for preparing a molybdenum-boron ion modified, cesium-doped Li-Al hydrotalcite solid electrolyte, characterized in that The following steps are involved: A.Cs + Preparation of Li-Al doped lithium aluminum hydrotalcite material: Li-Al hydrotalcite was prepared by hydrothermal method. Appropriate amount of Al(OH)3, LiCl, CsCl and deionized water were used as raw materials for hydrothermal reaction. The reactor was taken out and cooled to room temperature. The sample was centrifuged and washed. The solid sample was collected and dried. Finally, the dried solid was ground and sieved out fine powder to obtain Cs + Li-Al doped hydrotalcite powder. B. Cs + The doped Li-Al hydrotalcite powder is placed in a tablet pressing mold, and the powder is pressed into an electrolyte sheet on a tablet press. The sheet is cut and finally stored in a glove box to prevent moisture. Boron ions and molybdenum ions are injected into the electrolyte sheet using plasma technology, and then assembled into a solid-state battery to test its ionic conductivity and lithium ion mobility.

2. The method for preparing a molybdenum-boron ion modified, cesium-doped Li-Al hydrotalcite solid electrolyte according to claim 1, characterized in that: In step A, the mass ratio of Al(OH)3, LiCl, and CsCl is 1-2:4-6:0.05-0.

3.

3. The method for preparing a molybdenum-boron ion modified, cesium-doped Li-Al hydrotalcite solid electrolyte according to claim 1, characterized in that: In step A, the content of deionized water is 100-200 mL.

4. The method for preparing a molybdenum-boron ion modified, cesium-doped Li-Al hydrotalcite solid electrolyte according to claim 1, characterized in that: In step A, the hydrothermal temperature is 80-100° C. and the drying time is 1-2 days.

5. The method for preparing a molybdenum-boron ion modified, cesium-doped Li-Al hydrotalcite solid electrolyte according to claim 1, characterized in that: In step A, the sample is centrifuged and then washed three to five times with ice deionized water.

6. The method for preparing a molybdenum-boron ion modified, cesium-doped Li-Al hydrotalcite solid electrolyte according to claim 1, characterized in that: In step B, the diameter of the electrolyte sheet is about 16-19 mm.

7. The method for preparing a molybdenum-boron ion modified, cesium-doped Li-Al hydrotalcite solid electrolyte according to claim 1, characterized in that: In step B, the thickness is about 1-2 mm.

8. The method for preparing a molybdenum-boron ion modified, cesium-doped Li-Al hydrotalcite solid electrolyte according to claim 1, characterized in that: In step B, the operating frequency of the plasma processing equipment is 13.56-40.68 MHz.

9. The method for preparing a molybdenum-boron ion modified, cesium-doped Li-Al hydrotalcite solid electrolyte according to claim 1, characterized in that: In step B, the power of the plasma treatment is 500-2000 watts, and the treatment time is 1-5 minutes.

10. The method for preparing a molybdenum-boron ion modified, cesium-doped Li-Al hydrotalcite solid electrolyte according to claim 1, characterized in that: In step B, during the plasma treatment process, the atmosphere in the treatment chamber is maintained as an inert gas with a gas flow rate of 50-100 ml / min.

Citation Information

Cited By

  • Preparation method of modified LATP solid electrolyte based on ion implantation technology

    CN122418020A